BODY MASS INDEX (BMI) AS A FACTOR INFLUENCING POST SURGICAL EVENTS IN PATIENTS WITH CORONARY ARTERY BYPASS GRAFTING (CABG) - Mesgerani, Mohsen; Begum, Khyrunnisa (Journal of Postgraduate Medical Institute, 2011)
Objective: To study association between obesity and post surgical events such as length of ICU and hospital stay, morbidity and complications among CABG patients. Material and Methods: The study was conducted in Iran during June - November 2006. 219 patients of elective CABG participated. Data regarding anthropometric indices, surgical and Post surgical observations for total time for surgery, time of stay in ICU; total length of Hospital stay; time of mechanical ventilation and occurrence of complications were obtained. Results: Women were overweight (49.2%) and obese (34.4 %) in higher percentage than men (42.1 and 20.6%). Shoulder height; shoulder waist and waist height ratios were linearly proportional to increase in BMI. Waist hip ratio had poor association with BMI in both males and females (P< 0.5). Mean surgery time was 3.62 ± 0.553, 3.77 ± 0.522 and 4.22 ± 0.856 hrs for normal, over weight and obese patients. Mean ventilation time was significantly low (7. 64 ± 2.725 hrs.) for overweight subjects. Occurrence of Arrhythmia (34.7 Vs 2.7 %) delirium (11.6 & 4.0%), and need for re-intubation (9.3 and 0.0%) was also higher in obese. Mean time of ICU stay was 55.49 ± 18.381hrs, obese patients required significantly longer time (62.48 ± 20.494 hrs). This seemed to influence number of days in hospital. The mean morbidity rate was higher in ICU (22.0%) as compared to post surgical wards (1.2%). Subjects with normal BMI occupied the central position between obese and overweight subjects for most parameters. Conclusion: Overweight subjects exhibited better performance than those who were normal or obese signifying influence of body weight on post surgical prognosis. Presence of small proportion of adipose tissue probably buffers against the traumatic effects of surgery.